Increased vimentin in human α- and β-cells in type 2 diabetes. Issue 3 (June 2017) - Roefs, Maaike M; Carlotti, Françoise; Jones, Katherine; Wills, Hannah; Hamilton, Alexander; Verschoor, Michael; Williams Durkin, Joanna M; Garcia-Perez, Laura; Brereton, Melissa F; McCulloch, Laura; Engelse, Marten A; Johnson, Paul R V; et al.
Abstract : Type 2 diabetes (T2DM) is associated with pancreatic islet dysfunction. Loss of β-cell identity has been implicated via dedifferentiation or conversion to other pancreatic endocrine cell types. How these transitions contribute to the onset and progression of T2DM in vivo is unknown. The aims of this study were to determine the degree of epithelial-to-mesenchymal transition occurring in α and β cells in vivo and to relate this to diabetes-associated (patho)physiological conditions. The proportion of islet cells expressing the mesenchymal marker vimentin was determined by immunohistochemistry and quantitative morphometry in specimens of pancreas from human donors with T2DM ( n = 28) and without diabetes (ND, n = 38) and in non-human primates at different stages of the diabetic syndrome: normoglycaemic (ND, n = 4), obese, hyperinsulinaemic (HI, n = 4) and hyperglycaemic (DM, n = 8). Vimentin co-localised more frequently with glucagon (α-cells) than with insulin (β-cells) in the human ND group (1.43% total α-cells, 0.98% total β-cells, median; P < 0.05); these proportions were higher in T2DM than ND (median 4.53% α-, 2.53% β-cells; P < 0.05). Vimentin-positive β-cells were not apoptotic, had reduced expression of Nkx6.1 and Pdx1, and were not associated with islet amyloidosis or with bihormonal expression (insulin + glucagon). In non-human primates, vimentin-positive β-cell proportion was larger in the diabetic than the ND group (6.85 vs 0.50%, medians respectively, P < 0.05), but was similar in ND and HI groups. In conclusion, islet cell expression of vimentin indicates a degree of plasticity and dedifferentiation with potential loss of cellular identity in diabetes. This could contribute to α- and β-cell dysfunction in T2DM.